Rhetorik auf dem Schlachtfeld: Caesar, Pompeius und Labienus vor der Entscheidung bei Pharsalus (De Bello Civili III, 85–87) - Bär, Silvio (Hyperboreus, 2014)
Chapters 82–87 of Book III of Caesar’s Bellum civile depict the preparations before the Pharsalus battle. The narrator of the Bellum civile reproduces three speeches: by Caesar, by Pompey and by Titus Labienus. This paper analyses the content, structure and function of these three speeches with regard to the general characterisation of the two commanders-in-chief within the Bellum civile, and with a speciﬁc view to the subsequent course of events. Inter alia, the question is asked how the speeches foreshadow the following actions of Caesar and Pompey, and how they may be understood in the wider context of the possible intentions of the Bellum civile as such. It can be demonstrated that the narrator of the Bellum civile ‘navigates’ his reader through the text in a manipulative manner, so that Caesar appears in a decidedly positive way, whereas Pompey’s portrait is equally negative.